Speech Styles in Kelly Clarkson Show: Sociolinguistics Study - Daffa Muhammad Ivandharu; Heri Heryono (Budapest International Research and Critics University, 2022)
The main aim of this study is to analyze and investigate the speech styles are used by Kelly as the host of Kelly Clarkson Show to her younger and older guests and the factors that cause Kelly as the host of the Kelly Clarkson Show to use different speech styles to her younger and older guests. In this study, the descriptive qualitative analysis approach was used. Two Kelly Clarkson Show videos were used to gather the data. The results showed three types of speech styles used in the Kelly Clarkson Show with her younger guest: casual style (21%), formal style (21%), and intimate style (5%). As opposed to that, there are same three types of speech styles used in the Kelly Clarkson Show with her older guest with different percentages: casual style (26%), formal style (16%), and intimate style (11%). This study has the highest percentage of the sort of casual style, it can be said.